Which Microenterprises have High Returns to Capital? - McKenzie, David (World Bank, Washington, DC, 2012)
This new series is intended to share the findings of impact evaluations in the areas of finance and private sector development (FPD) that researchers in Finance and Private Sector Development Team of the Development Research Group (DECRG-FP) have been involved in, and to draw out their lessons for operational staff and policymakers. Rigorous evaluations of FPD policies are relatively rare compared to other sectors such as health and education, and there is often a perception that many FPD projects do not lend themselves to serious evaluation. The hope going forward is to showcase examples where assessment has been possible, and to enhance operational interest in evaluations of upcoming projects.